Integration of remote sensing and geochemical analysis of chromite bodies in the Logar Ophiolitic Complex, Southeast Afghanistan (Kuwait Journal of Science)
Chromite, a significant mineral for chromium, is extensively dispersed toward the southeast and east regions of Afghanistan, particularly in Logar Province. Hosted in the lowest ultramafic rocks of the Logar Ophiolite Complex (LOC), the podiform-type chromite mineralization showcases varying textures from massive chromite pods to disseminated chromite crystals. The ultramafic rocks, predominantly dunite and harzburgite, are serpentinized, with chromite found microscopically exhibiting a granular texture. This study focuses on geochemical analysis to discern the petrology and mineralogy of chromite in the LOC, utilizing Landsat 8 Operational Land Imager (OLI). Through the False Color Composite (FCC) technique and Landsat 8 data, approximately 40 % of the Mohammad Agha district in Logar Province is identified as containing chromite bodies. The fieldwork validated Landsat 8 results, confirming the efficacy of the applied techniques. X-ray fluorescence (XRF) data further reveal that the mean percentage of chromite oxide within the studied samples ranges from 35 to 40 %. This integrated approach, combining Remote sensing (RS) and geochemical analysis, not only characterizes chromite occurrences but also contributes to improving lithological mapping, offering valuable insights for geological research and resource exploration. © 2025 The Authors